2014
DOI: 10.18632/oncotarget.2117
|View full text |Cite
|
Sign up to set email alerts
|

The response of head and neck squamous cell carcinoma to cetuximab treatment depends on Aurora kinase A polymorphism

Abstract: ObjectivesThe aim of this study was to evaluate the efficiency of cetuximab-based anti-EGFR treatment and Aurora kinase A / B knockdown as a function of Aurora kinase polymorphism in HNSCC cell lines.Materials and methodsFirst, protein expression of Aurora kinase A / B and EGFR and Aurora kinase A polymorphism were studied in tumour samples.The survival and proliferation of Aurora kinase A homo- (Cal27) and heterozygous (HN) HNSCC cell lines was evaluated using a colony formation assay and a flow cytometric as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 41 publications
2
22
1
2
Order By: Relevance
“…Various strategies have been developed to disrupt EGFR function and to interfere with downstream signaling ( 11 , 12 ). Anti-EGFR mAbs and EGFR inhibitors have been investigated the most extensively ( 3 , 5 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been developed to disrupt EGFR function and to interfere with downstream signaling ( 11 , 12 ). Anti-EGFR mAbs and EGFR inhibitors have been investigated the most extensively ( 3 , 5 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Aurora-Kinase C is mainly expressed in the testicles and supports the Aurora-Kinase B function [ 3 ]. Elevated Aurora-Kinase expression has been found in a number of malignancies [ 4 ], amongst them HNSCC [ 5 , 6 ]. Moreover, it has been shown that the AurkA Phe 31 -Ile polymorphism enhances esophageal cancer progression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the receptor should be internalized and down-regulated, leading to the inhibition of downstream signaling cascade [21]. This paradoxical phosphorylation of EGFR by Cetuximab treatment has been described in the literature [22, 23]. …”
Section: Discussionmentioning
confidence: 99%